Walkability Index in Commercial Area of Pangkalpinang City - Revy Safitri; Ririn Amelia (Jurnal Infrastruktur, 2019)
One of the commercial areas in Pangkalpinang City is located in Pangkalpinang Plaza - Bangka Trade Center Area. As a commercial area, this area generates a large number of trips. Trip attractions towards this area are not only vehicle trips but also trips of the pedestrians. The trips of pedestrians in this area require pedestrian facilities. Evaluation of pedestrian facilities needs to be carried out to provide adequate pedestrian facilities. Pedestrian facilities can be evaluated based on walkability assessments. This study aims to evaluate the pedestrian facilities in Pangkalpinang Plaza - Bangka Trade Center Area through walkability index assessment. In measuring the walkability index, the pedestrian routes in this area are divided into 16 road segments. Then, the walkability index will be assessed using 9 parameters in each road segment. In this study, the walkability index assessment was carried out by comparing assessments based on the inventory of pedestrian facilities and based on perceptions of pedestrians. The results show that Pangkalpinang Plaza - Bangka Trade Center Area is in bad condition for walking. Besides that, this research reveals both based on an inventory of pedestrian facilities and based on pedestrian perceptions, that the disability infrastructure is not yet available. The results of this study also show that most of the parameters are not good enough, so it is necessary to improve pedestrian facilities. Furthermore, the results of this study can be used as a consideration of the government for improving pedestrian facilities in Pangkalpinang Plaza - Bangka Trade Center Area.